Inverted U-shaped relationship between serum 25-hydroxyvitamin D concentrations and Toxoplasma gondii infection: a cross-sectional study - Huang, Lihua; Luo, Xiaoyan; He, Liuliu; You, Xiaoyan; Chen, Xiaobo (Frontiers in Public Health, 2024)
Toxoplasma gondii (T. gondii) is a widespread zoonotic parasite transmitted through contaminated food or water. It poses a significant public health threat, especially to pregnant women and immunocompromised individuals. 25-Hydroxyvitamin D [25(OH)D] plays a critical role in regulating both innate and adaptive immune responses, particularly in its anti-infective capacity.However, the relationship between serum 25(OH)D concentrations and T. gondii infection remains uncertain.We analyzed the data from the National Health and Nutrition Examination Survey (NHANES) spanning 2009-2014 to explore the association between serum 25(OH)D concentrations and T. gondii infection. Extensive demographic, comorbidity, and dietary data were collected. The status of T. gondii infection was determined using serum anti-IgG antibodies. Serum 25(OH)D levels were measured using ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC- MS/MS). In addition, weighted logistic regression and restricted cubic spline analyses were performed.Our analysis included 10,157 participants (mean [SE] age, 45.38 [0.39] years; 49.73% female) who met the inclusion criteria. Serum 25(OH)D levels were categorized into quintiles, with the second quintile serving as the reference group. The final model, adjusted for age, sex, race, education level, poverty income ratio, body mass index, smoking status, hypertension, diabetes, chronic kidney disease, depression, physical activity, alcohol intake, seasonal testing, and dietary vitamin D, revealed the following adjusted odds ratios (ORs) for the quintiles: 0.73 (95% confidence interval[CI]: 0.60-0.93) for the first, 0.87 (95% CI: 0.69-1.10) for the third, 0.75 (95% CI: 0.58-0.95) for the fourth, and 0.66 (95% CI: 0.49-0.91) for the fifth. Additionally, a restricted cubic spline analysis revealed an inverted U-shaped relationship between serum 25(OH)D and T. gondii infection, with an inflection point at approximately 51.29 nmol/L. Odds ratios to the left and right of the inflection point were 1.22 (95% CI: 1.10-1.35) and 0.91 (95% CI: 0.85-0.97) per 10 nmol/L, respectively.Our study uncovers an inverted U-shaped relationship between serum 25(OH)D concentrations and T. gondii infection, with an inflection point around 51.29 nmol/L.